Identification of superior high yielding sunflower (Helianthus annuus L.) hybrids for rabi-summer season in West Bengal: IDENTIFICATION OF HIGH YIELDING SUNFLOWER HYBRIDS FOR RABI-SUMMER IN WEST BENGAL - S S LAKSHMAN; D K ROY; Y G SHADAKSHARI (Journal of Oilseeds Research, 2018)
An experiment was carried out during 2012-13 to 2014-15 at Nimpith Centre of Ramkrishna Ashram Krishi Vigyan Kendra Research Farm, West Bengal to identify suitable sunflower hybrids for rabi-summer season. A total of 150 sunflower hybrids were tested including two National check hybrids (KBSH-44 and DRSH-1). The field observation revealed that the hybrid PSCHT-12-38 (2260 kg/ha, 36.0% oil content), PSCHT-12-42 (2250 kg/ha, 37.5% oil), PSCHT-12-26 (2217 kg/ha, 37.7%) and PSCHT-12-36 (2151 kg/ha, 37.9% oil content) recorded higher seed yield as well as high oil content in comparison to the national check hybrids. The new experimental hybrids viz.,PSCHT-12-42,SAHT-12-09,PSCHT-12-26, PSCHT-12-36, PSCHT-12-38, PSCHT-12-66,PSCHT-12-76 and PSCHT-12-29 were tolerant to sunflower wilt (PDI score 10-12.5%) in comparison to the checks (PDI score 20-25%). Considering the other yield attributing parameters like plant height, days to 50% flowering or days to maturity, hull content and volume weight, hybrids like PSCHT-12-38, PSCHT-12-42 , PSCHT-12-26 and PSCHT-12-36 were promising due to their 7-10 days earliness and 30-50 cm shorter plant height at harvest coupled with good seed yield and oil yield as well as high degree of tolerance to sunflower wilt.